DOSES DE POTÁSSIO NA REDUÇÃO DA PODRIDÃO RADICULAR SECA DO FEIJOEIRO. - COSTA, Brenda Fernandes,; PESSÔA, Guilherme Martins,; ROSA, Artur Guerra,; MIRANDA, Hevelâyne Cristina Ferreira,; SANTOS, Stephany,; GRAICHEN, Felipe André Sganzerla, (ANAIS DO ENIC, 2022)
-